2006
DOI: 10.1002/uog.3801
|View full text |Cite
|
Sign up to set email alerts
|

Re: Feasibility and reproducibility of an image‐scoring method for quality control of fetal biometry in the second trimester

Abstract: CorrespondenceRe: Feasibility and reproducibility of an image-scoring method for quality control of fetal biometry in the second trimester I would like to congratulate the authors of a recent paper in this journal on the feasibility of an image scoring method for quality control of fetal biometry in the second trimester 1 . They have made a valuable contribution to the literature in an area of work that is too often neglected, and have carefully addressed the areas of intra-and interobserver reproducibility. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The sonographers in our study compiled their own portfolios, which resulted in awareness of image acceptability and lacking images. Previous studies showed that a sonographer's own assessment of image acceptability facilitated quality improvement . Most sonographers with an inadequate score acknowledged the judgment of the auditor during the audit visit, realizing that failing to continuously keep adapting the magnification and the correct plane of a structure during the scan of a moving fetus results in the storage of inadequate images.…”
Section: Discussionmentioning
confidence: 99%
“…The sonographers in our study compiled their own portfolios, which resulted in awareness of image acceptability and lacking images. Previous studies showed that a sonographer's own assessment of image acceptability facilitated quality improvement . Most sonographers with an inadequate score acknowledged the judgment of the auditor during the audit visit, realizing that failing to continuously keep adapting the magnification and the correct plane of a structure during the scan of a moving fetus results in the storage of inadequate images.…”
Section: Discussionmentioning
confidence: 99%